2016
DOI: 10.1186/s13567-016-0398-x
|View full text |Cite
|
Sign up to set email alerts
|

Oestrous cycle-dependent equine uterine immune response to induced infectious endometritis

Abstract: Infectious endometritis is a major cause of reduced pregnancy rates in horses. The objectives of this study were to establish a timeline of the innate immune response in the uterus of healthy horses and to investigate the oestrous cycle effect on this. Endometrial biopsies were collected from five horses before and at 3, 12, 24, 48 and 72 h after inoculation of Escherichia coli, once in oestrus and once in dioestrus. They were analysed by quantitative real-time PCR, microbiology and histology. Neutrophil numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 57 publications
1
25
0
Order By: Relevance
“…In agreement with other studies (Crossett, Allen, & Stewart, ; Hayes et al, ), P19/uterocalin (also known as concepticalin, equicalin and lipocalin P19) was found to be more abundant in endometrial flush fluid samples from mares in dioestrus. Studies on endometrial mRNA expression of uterocalin in mares have also indicated greater expression in dioestrus than in oestrus (Marth et al, ). Uterocalin is a P 4 ‐dependent protein that is secreted by endometrial glands both in dioestrus and early pregnancy (Crossett et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with other studies (Crossett, Allen, & Stewart, ; Hayes et al, ), P19/uterocalin (also known as concepticalin, equicalin and lipocalin P19) was found to be more abundant in endometrial flush fluid samples from mares in dioestrus. Studies on endometrial mRNA expression of uterocalin in mares have also indicated greater expression in dioestrus than in oestrus (Marth et al, ). Uterocalin is a P 4 ‐dependent protein that is secreted by endometrial glands both in dioestrus and early pregnancy (Crossett et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…have also indicated greater expression in dioestrus than in oestrus (Marth et al, 2016(Marth et al, , 2018. Uterocalin is a P 4 -dependent protein that is secreted by endometrial glands both in dioestrus and early pregnancy (Crossett et al, 1996).…”
Section: Studies On Endometrial Mrna Expression Of Uterocalin In Maresmentioning
confidence: 99%
“…Given the high expression of ß defensin 4 (human gene name DEFB4 ) in IL-17-treated human keratinocytes [34], we used qPCR to examine relative expression levels of DEFB4B mRNA in SLL samples compared to non-laminitic controls (Fig 4). Note that the equine DEFB4B sequence was formerly identified as ß defensin 1 [61]. As shown in Fig 4A, DEFB4B expression was upregulated at all disease stages compared to the non-laminitic controls.…”
Section: Resultsmentioning
confidence: 90%
“…In addition, Marth et al found that the expression of the NLRC5 increased significantly within 3 hours in response to the introduction of E. coli. And this finding also indicated that the introduction of E. coli into the uterus of healthy animal has an effect on inducing inflammation, which was an effective model of innate immunity as well (Marth et al, 2016). Moreover, numerous studies have provided evidence that common variations in the NLR genes were highly correlated to the incidence of intestinal inflammation as well as susceptibility to cancer (Ogura et al, 2001; Villani et al, 2009; Kutikhin, 2011; Jostins et al, 2012).…”
Section: Biological Functionsmentioning
confidence: 89%